As telenovelas Mar do Sertão (2022) e Travessia (2022): imaginários nordestinos em circulações midiatizadas no X - Viana, Núbia Andrade; da Rosa, Ana Paula; Nogueira, Cícero Brito (Anais de Artigos do Seminário Internacional de Pesquisas em Midiatização e Processos Sociais; Vol 1 No 6 (2024): Anais de Artigos do VI Seminário Internacional de Pesquisas em Midiatização e Processos Sociais - Anthropocene, classifications and environment: perspectives from mediatization, 2024)
This research aims to understand how imaginaries of the Northeast circulate on the social network X, based on posts about the soap operas Mar do Sertão and Travessia. To this end, our problem is how the imaginary meanings created by social actors about the telenovelas mentioned circulate on the platform. The authors studied include: Fausto Neto, Pedro Gomes, Ana Paula da Rosa, Martin-Barbero and Eliseo Verón. The methodology used is based on observing the media circuits and analyzing the topics covered, based on their relationship with Northeastern stereotypes. The first conclusions are that reading contracts have been broken in relation to disbelief in certain narratives and the association with reality in some publications.